2022
DOI: 10.1016/j.jhazmat.2022.128279
|View full text |Cite
|
Sign up to set email alerts
|

Link between SARS-CoV-2 emissions and airborne concentrations: Closing the gap in understanding

Abstract: The airborne transmission of SARS-CoV-2 remains surprisingly controversial; indeed, health and regulatory authorities still require direct proof of this mode of transmission. To close this gap, we measured the viral load of SARS-CoV-2 of an infected subject in a hospital room (through an oral and nasopharyngeal swab), as well as the airborne SARS-CoV-2 concentration in the room resulting from the person breathing and speaking. Moreover, we simulated the same scenarios to estimate the concentration of RNA copie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Outside of the laboratory, signs of viable SARS‐CoV‐2 in the air have been detected, 10‐12 and the virus has also been cultured from exhaled air 13 . A direct link between SARS‐CoV‐2 viral load, emission, and airborne concentration was recently demonstrated by Buonanno et al 14 A few studies have detected SARS‐CoV‐2 RNA in the air at home‐environment 15,16 . In hospitals, PCR‐based studies have found SARS‐CoV‐2 RNA in room air, 17‐25 as well as from air conditioning filters located over 50 m from the patient room 26 .…”
Section: Introductionmentioning
confidence: 94%
“…Outside of the laboratory, signs of viable SARS‐CoV‐2 in the air have been detected, 10‐12 and the virus has also been cultured from exhaled air 13 . A direct link between SARS‐CoV‐2 viral load, emission, and airborne concentration was recently demonstrated by Buonanno et al 14 A few studies have detected SARS‐CoV‐2 RNA in the air at home‐environment 15,16 . In hospitals, PCR‐based studies have found SARS‐CoV‐2 RNA in room air, 17‐25 as well as from air conditioning filters located over 50 m from the patient room 26 .…”
Section: Introductionmentioning
confidence: 94%
“…This volumetric state variable was chosen because of its potential to be used to estimate infection risk mechanistically (though such estimation of infection risk was left for future work). Previous modeling studies have performed such “bottom-up” estimations by (1) combining estimates of particle volume with empirical data on viral load to derive corresponding viral doses and then (2) combining these viral dose estimates with empirically derived dose–response relationships to estimate infection risks. , There are several uncertainties in estimating viral dose and corresponding infection risk based on particle volume, which are discussed in the Discussion section.…”
Section: Methodsmentioning
confidence: 99%
“…The COVID pandemic has thrust a spotlight on the relationship between indoor ventilation and disease transmission, where there is now exceptionally strong evidence that the pathogen responsible for COVID infection is transmitted primarily via respirated particles suspended in air (Morawska and Milton, 2020;Buonanno et al, 2022). Based on scientific evidence in this area, OzSAGE, an organization of scientists providing independent advice to the Australian government, advises that:…”
Section: Covid and E Ect Of Poor Iaq On Disease Transmissionmentioning
confidence: 99%
“…The relationship between poor IAQ and reduced productivity, concentration and decision making ability has long been identified in classrooms (Fisk, 2017) and offices (Wargocki and Wyon, 2013;Zhang et al, 2017). Yet the COVID pandemic has thrust the importance of room ventilation into the international spotlight, as the disease is proven to be more readily transmitted through particulates exhaled in human breath than through touching contaminated surfaces (Morawska and Milton, 2020;Buonanno et al, 2022;Gulland, 2022). Classrooms have remained of particular interest to air quality scientists pre-and during-COVID, given their high occupant densities and consideration given to children's developing respiratory systems (Gurdasani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%